Correlation between the level of education and the adequacy of cervical excisional procedures in patients with cervical preinvasive lesions - Ceylan, Yasemin; Api, Murat; Kabaca Kocakuşak, Canan; Keleş, Erhan; Akış, Serkan; Purut, Yunus Emre; Giray, Burcu; Güray Uzun, Mine (BMJ Publishing Group, 2019)
[Abstract Not Available]
Keywords: Cervical Excisional; Cervical Preinvasive Lesions; Adequacy